A modelling approach to evaluate land management options for recently burnt catchments. (17th July 2022) - Basso, Marta; Serpa, Dalila; Rocha, João; Martins, Martinho A. S.; Keizer, Jacob; Vieira, Diana C. S.
Abstract: Scars left by wildfires are easily visible in the Mediterranean landscape and, like any wound, even those left by fires must be treated to regenerate properly. If not managed, spontaneous vegetation regeneration will eventually cover the affected area, restoring the hydrological cycle. The reforestation of burned stands, involving ploughing the land and building terraces on steep slopes, together with fertilisation of the area, is also common. The Soil and Water Assessment Tool (SWAT) was used to simulate three post‐fire land management options for a small catchment in central Portugal. The choice of this basin relates to the implementation of terraces to create a eucalyptus forest production area 7 months after a fire completely burned the catchment. Two alternative post‐fire scenarios were designed, one simulating the spontaneous recovery of the ecosystem and the second reproducing a catchment‐scale implementation of a highly effective erosion mitigation measure (mulching). Then, the mulch scenario and the actual eucalyptus cycle were compared with the spontaneous recovery scenario to appraise the best management choice. The post‐fire and post‐terracing periods showed a satisfactory agreement between simulated and observed daily parameters. Concerning the management alternatives evaluated, mulching and terracing reduced soil loss and sediment transported in streams compared to spontaneous recovery. However, higher flow volumes and phosphorus exports were predicted under terraced conditions, likely due to increased infiltration capacity and accelerated leaching processes, raising concerns about stream water quality. These findings can be applied to other Mediterranean catchments affected by wildfires and in which post‐fire management actions are planned, making stakeholders aware of the impacts and uncertainties of post‐fire scenarios, thus improving the management of burnt areas. Highlights: Calibration of SWAT model for three different post‐fire management practices. Satisfactory model performance in simulating water quantity and quality for both periods. Spontaneous recovery evidenced high soil losses during all the simulated period. The implementation of terraces and the application of mulch reduced sediment transport.